The Video Tutorials as Learning Media to Improve Basic Dribbling and Shooting Techniques in Soccer Games - I Made Abdi Setiawan; Made Agus Dharmadi; Kadek Yogi Parta Lesmana (Universitas Pendidikan Ganesha, 2025)
The limited availability of instructional materials that can foster students’ activeness and critical thinking skills remains a challenge in Physical Education, Sports, and Health (PESH) learning, particularly in teaching basic motor skills in soccer. This study aims to analyze and develop a video tutorial-based learning medium focusing on basic dribbling and shooting techniques as an effort to improve the quality of the PESH learning process. This research employed a research and development approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects included media experts, instructional design experts, subject matter experts, field practitioners, and 24 sixth grade students who participated as product trial respondents. Data were collected using questionnaires developed based on media feasibility instrument indicators and analyzed using descriptive quantitative techniques in the form of percentages. The results showed that the video tutorial-based learning media achieved a very good category, with feasibility scores of 94.1% from media experts, 100% from instructional design experts, 92.9% from subject matter experts, and 96.7% from field practitioners. Student trial results indicated feasibility levels of 90.6% in individual trials, 89.2% in small group trials, and 93.1% in large group trials. These findings confirm that the developed video tutorial media demonstrates a high level of validity and feasibility and is suitable for use in PESH learning. This study implies the strengthening of video tutorial-based media utilization as an alternative instructional resource that supports more effective and student-centered learning.